Home automation system using parallel port / Muhamad Syahrizam Salidin - Salidin, Muhamad Syahrizam (2005)
The main purpose of this project is to help users how to control their electrical appliances while they are not at home through the control timer. This project focused on the developing home automation system in Windows platform. The home apphances can be controlled through parallel port on Personal Computer (PC) by program developed using software for example Microsoft Visual Basic. The home appliances and the PC can be accessed and controlled via parallel port cable by a Home Automation System program. Parallel port interface circuit was constructed for the purpose of the controlling the appliances. Basically the parallel port is to be used as a media inter&ce in this controlling purpose. The parallel port is a very simple and affordable technique in controlling external circuitry. With just a D-Type 25 Pin Male Connector, buffers, relays and simple wiring, the computer can be interfaced to the external devices.